2020
DOI: 10.37358/rc.20.5.8146
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Using Mineral Fertilization Combined with Sewage Sludge in the Amendment of Luvisol on Oat Crop. II. Influence on Metal Accumulation

Abstract: The objective of the present paper was to investigate the effects of sewage sludge application on metals (Cu, Mn, Zn, Cd, Co, Pb) accumulation in oat (Avena sativa L.) grains, Somesan variety. It were used various doses of sewage sludge corresponding to equivalent doses of 0-600 kg N/ha associated or not with NPK mineral fertilization. The results evidenced that copper and zinc levels in oat grains increased significant with sewage sludge fertilization starting with a dose equivalent with 200 kg N/ha. Mineral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Furthermore, it has been observed that on andosols, heavy metals are exclusively of paedogenetic origin (derived from the parent material in the pedogenesis processes), and their natural geochemical associations are undisturbed. On anthroposols, heavy metals are mostly of anthropogenic origin, and the degree of stabilization of geochemical associations is relatively low, being determined by the form of entry of heavy metals into the soil and their residence time (Mihalache et al, 2014;Huang et al, 2019). The analysis of the data presented in Table 2 shows that the average values of the heavy metal content increased by several units compared to other chromic soils studied by us and previously published in other journals.…”
Section: Heavy Metals Contents In the Chromic Luvisols Under Agricult...mentioning
confidence: 73%
See 2 more Smart Citations
“…Furthermore, it has been observed that on andosols, heavy metals are exclusively of paedogenetic origin (derived from the parent material in the pedogenesis processes), and their natural geochemical associations are undisturbed. On anthroposols, heavy metals are mostly of anthropogenic origin, and the degree of stabilization of geochemical associations is relatively low, being determined by the form of entry of heavy metals into the soil and their residence time (Mihalache et al, 2014;Huang et al, 2019). The analysis of the data presented in Table 2 shows that the average values of the heavy metal content increased by several units compared to other chromic soils studied by us and previously published in other journals.…”
Section: Heavy Metals Contents In the Chromic Luvisols Under Agricult...mentioning
confidence: 73%
“…The parent material on which it was formed is generally composed less often of loess deposits, with the predominance of marly deposits and marly clays which hinder the internal drainage capabilities of the soil. The puddle phenomenon is also manifested due to the compaction of the land, under the continuous action of the equipment and machines used for agriculture (Mihalache et al, 2014).…”
Section: Spread Of Chromic Luvisolsmentioning
confidence: 99%
See 1 more Smart Citation